Entre a loucura e a norma: mulheres internadas no Sanatório Pinel (São Paulo, 1929-1944) - Pereira, Bruna dos Santos Beserra (2016)
This research investigates the history of women diagnosed as insane and put in Pinel Sanatorium between the years of 1929 and 1944. Through either medical records produced on that institution and writings from doctor Pacheco e Silva, the Sanatorium's founder and director, it is intended to track the profiles to be considered as rule deviants, problematising, thus, the patterns conceived for the women. These histories have been developed within the city of Sao Paulo; therefore it became necessary to elaborate a city panorama in its modernising perspective, highlighting its urbanization process and the intervention of medicine in the urban constitution. The city's modernising project is related to the institutionalisation of mental institutions, as well as the increasing presence of the medical speech, intending to a standardisation of behaviours both in the public and private space. Thus, there is the question to the social roles attributed to women, which concern their responsibility due to the family and the formation of future citizens, being their social function attached to biological/breeding aspects, outlining then the existing discourse concerning womanhood, wifehood attributions, motherhood attributions and to be a housewife as the natural fate to women, as opposed to the implemented restriction to other possibilities of female experiences, being these identified as deviant, abnormal and pathological